Horizontal agreements about the use of a natural resource - Geert Van Moer (Helsinki Graduate School of Economics, 2023)
This paper studies sustainability agreements between competitors about their use of a natural resource. A symmetric Cournot duopoly model reveals the main effects. Two types of agreements are considered, specifying (1) the absolute usage of the natural resource per firm and (2) the relative usage of the natural resource, per unit of production. Whenever an agreement induces substitution towards other resources, production quantities decline. An agreement about the relative usage of the natural resource is ineffective unless returns to scale are decreasing. I argue that returns to scale are decreasing particularly in the short run after an agreement is made.
Keywords: L13; L41; Q01; Q38; 330; sustainability agreements; natural resources